Development of a multi-epitope chimeric vaccine in silico against Babesia bovis, Theileria annulata, and Anaplasma marginale using computational biology tools and reverse vaccinology approach - AMAM Zonaed Siddiki; Sabreena Alam; Farhan Fuad Bin Hossen; Md. Abdul Alim (PLoS ONE, 2025)
The three rickettsial parasites- Babesia bovis, Theileria annulata and Anaplasma Marginale are responsible for causing Babesiosis, Theileriosis and Anaplasmosis among cattle. These diseases exist due to spreading of infected ticks. A large number of cattle were found to suffer from mixed infections caused by the three parasites at the same time. Due to these reasons cattle have been devoid of milk production with reduced meat availability. Hence, it is a matter of urgency for the immunity of cattle to exhibit resilience against all three rickettsial parasites. It could be possible if trials are carried out after producing a subunit chimeric vaccine against the rickettsial protozoan parasites and introducing it into the bloodstream of the cattle species. In this paper, we have used the process of reverse vaccinology to conduct a study in which we have developed a multi-epitope subunit chimeric vaccine against three protozoan parasites. We constructed three chimeric vaccine sequences from which only one chimeric vaccine construct was found to be an effective and efficient vaccine which is stable with high solubility and negative allergenicity. Following that, we performed molecular docking of the refined chimeric vaccine construct with Rp-105 and TLR-9. It was observed that the chimeric vaccines interacted with the receptors with high binding energy. Immune simulation was also performed to determine the potentiality of the chimeric vaccine for eliciting an immune response. The best-designed chimeric vaccine construct was then reverse transcribed and adapted for the host E. coli K12 strain which was later inserted into the pET28a (+) vector for the cloning and expression of the vaccine. The study could be a good initiative for the development of an effective chimeric vaccine against bovine parasites.